KEPUTUSAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH MAGELANG DALAM MEMILIH PROGRAM STUDI - Hidayati, Luk Luk Atul; Pramita, Yulinda Devi (Universitas Muhammadiyah Magelang, 2019)
This study empirically tested and analyzed the decision-making factors of UMMagelang Faculty of Economics and Business students in choosing study programs. These factors include the image of tertiary institutions, interests, joint decisions, availability of jobs, sources of public information, and Word of Mouth (WOM) on the decision making of prospective students of the Faculty of Economics and Business UMMagelang to choose study programs.The sample used in this study was an early semester student at the management and accounting study program of FEB UMMagelang. The sample of semester 2 students is because they are classified as new students and can still be measured and identified their interest in choosing study programs at FEB UMMagelang. The results showed that the WOM method influenced the decision to choose a study program. It means that many of FEB UMMagelang students are often involved in communication and talking about FEB UMMagelang. Brand image is one of the considerations of prospective students of the Faculty of Economics and Business, University of Muhammadiyah Magelang, choosing study programs at FEB UMMagelang. The joint decision to choose the bachelor program (S-1) at the Faculty of Economics and Business, University of Muhammadiyah Magelang also influenced the decision to vote. This shows that the role of parents and family influences the decision to choose study programs at the Faculty of Economics and Business, University of Muhammadiyah Magelang.